2002
DOI: 10.1159/000057712
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Jaundice Alters CD44 Expression in Rat Small Intestine

Abstract: Hypothesis: CD44 is an adhesion molecule expressed by neutrophils, lymphocytes and epithelial cells. CD44 is involved in cell-cell and cell-matrix binding. In addition to lymphocyte trafficking, CD44 also plays a crucial role in the maintenance of intestinal villus integrity. We hypothesize that obstructive jaundice may alter CD44 expression in the rat small intestine and oral glutamine intake can restore the altered CD44 expression in the small intestine of the rat undergoing obstructive jaundice. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This distribution of the CD44 expression corresponds to that of the regions of the epithelium undergoing cell division [9,10] . When any pathological condition (such as ischemia-reperfusion injury, obstructive jaundice, immunological bowel disease, and small-bowel allograft rejection) occurs in the gut, the CD44 expression is affected, thus immune and barrier functions of the mucosa are impaired [7,[19][20][21] . It has been reported [10] that the regulatory mechanisms and the physiological role underlying the expression of CD44 on intestinal epithelial cells may be due to the localized production of cytokines such as interferon gamma and tumor necrosis factor alpha.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distribution of the CD44 expression corresponds to that of the regions of the epithelium undergoing cell division [9,10] . When any pathological condition (such as ischemia-reperfusion injury, obstructive jaundice, immunological bowel disease, and small-bowel allograft rejection) occurs in the gut, the CD44 expression is affected, thus immune and barrier functions of the mucosa are impaired [7,[19][20][21] . It has been reported [10] that the regulatory mechanisms and the physiological role underlying the expression of CD44 on intestinal epithelial cells may be due to the localized production of cytokines such as interferon gamma and tumor necrosis factor alpha.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported [10] that the regulatory mechanisms and the physiological role underlying the expression of CD44 on intestinal epithelial cells may be due to the localized production of cytokines such as interferon gamma and tumor necrosis factor alpha. Sheen-Chen et al [7] demonstrated that 1 week of obstructive jaundice initially upgraded the CD44 expression in the rat small intestine, but after 2 weeks the CD44 expression became significantly decreased. We found similar results with respect to the CD44 expression in the rat small intestine after 2 weeks of obstructive jaundice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using sterile techniques, a mid-line incision was made, the common bile duct was identified, double-ligated with 5-0 silk, and divided between the two ligatures [17][18][19][20][21][22][23]. Shamoperated animals had the common bile duct freed from the surrounding soft tissue without ligation and transection.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…Using sterile techniques, a mid-line incision was made, and the common bile duct was identified, double-ligated with 5-0 silk, and divided between the two ligatures [16][17][18][19][20]. Sham-operated animals had the common bile duct freed from the surrounding soft tissue without ligation and transection.…”
Section: Operative Proceduresmentioning
confidence: 99%